Randomized Clinical Trial of LigaSure Haemorrhoidectomy versus Open Diathermy Haemorrhoidectomy (Journal of Armed Forces Medical College, Bangladesh, 2015)
Introduction: Haemorrhoidectomy is the most effective and definitive treatment for grade III or IV haemorrhoids. The traditional surgical approaches include the open (MilliganMorgan) and the closed (Ferguson and Parks) haemorrhoidectomy. Both procedures entail similar complications, in particular protracted postoperative pain that causes longer hospital stays. Recently, a variety of instruments have been used in an attempt to reduce postoperative pain and a quicker return to normal activities. A new option in performing Milligan -Morgan haemorrhoidectomy involves the LigaSure system, a bipolar electrothermal vessel sealing device.Objective: The randomized clinical trial was carried out to see the benefits of using LigaSure over monopolar diathermy in haemorrhoid surgery in terms of operating time, postoperative pain and complications.Materials and Methods: This randomized clinical trial was carried out in the Department of Surgery at Combined Military Hospital, Dhaka. The study was conducted for a period about two years. The sample size was one hundred cases of haemorrhoidectomy divided into 50 cases of two groups, which is LigaSure haemorrhoidectomy and open diathermy haemorrhoidectomy. Patients were included in the trial if they had symptomatic prolapsing internal haemorrhoids. All patients were randomized using sealed envelopes. Patients were blinded to the type of surgery performed. Patients kept a record of postoperative pain by means of a visual analogue scale. Symptom control and patients satisfaction were assessed at 12 weeks follow-up. LigaSure haemorrhoidectomy was performed by the mediumsized LigaSureTM forceps.Results: The operating time was less in LigaSure haemorrhoidectomy (mean 7.7 min with range of 4 to 16min) as compared with open diathermy haemorrhoidectomy (mean 18.2 with range 7-24 min) (p